DIRECTIONS INCREASING FINANCIAL SUSTAINABILITY OF ENTERPRISES IN THE CONDITIONS INDEPENDENT REGION - Melnychuk, Yu.M. (The actual problems of regional economy development, 2020)
The article “Directions Increasing Financial Sustainability of Enterprises in the Conditions Independent Region” at studying the financial sustainability of the enterprise, ways to achieve it in an independent region in Ukraine. The purpose of the article is to analyze the financial sustainability of the enterprise as a component of the economic sustainability of the independent region. The set of research methods was used in the work, which is the methodology of analysis and organization of major publications, legislation and laws, namely the methods of generalization, comparison, chronology, analysis and generalization. A complex system of financial transformations in the form of a petal chart using markers using Microsoft Excel is used. The article considers the concept of "economic sustainability", which allows us to fully understand the importance of financial sustainability of the enterprise, as an integral part of it, in an autonomous region. The importance of social sustainability in the structure of economic sustainability as a central and most important factor in the formation of business and the state economy is proved. The results of the study were the conclusions made on the basis of research of scientific and legislative base of research on this issue, as well as the formation of the main directions of increasing financial sustainability on the basis of social sustainability, which formed a scientific novelty in economic research. The practical significance of scientific research and its results is the financial analysis of the food market as a key indicator of welfare, as the formation of society is the main link to which the supply of any market. This is the basis for the formation of an independent region at the center of which is the human need for socio-economic benefits. It is proposed to deepen research in the direction of social sustainability as one of the main factors influencing the economic sustainability of the enterprise.